My Small Apple Has Rolled Away: Poetic Peculiarities of Funeral Laments for Children in Ukrainian and South Slavic Folklore Traditions - Mykytenko, Oksana (Tautosakos darbai, 2020)
Traditional notions about death at a young age shape the special character of funeral rituals for children and are reflected in associated funeral lamentations. These funerals are generally subject to the most mournful sympathy and sincere grieving owing to the emotional basis of the texts. At the same time, it was not common to mourn after the death of a baby or the first child. It is evident that there is a tendency to enhance the social status and the age of the dead child through ritual, e.g. by using specific vestments. The motif of the death-wedding seems to be the most relevant in this cycle. We also examine the traditional opposition of male / female children (especially evident in the South Slavic folklore tradition), reflected on the lexical level. The poetic style of the text is based mainly on two artistic “codes” – vegetal symbolism (metaphors of withering etc.) and zoological symbolism. The stylistics and composition found in these mourning rituals are characteristic of improvised folklore texts.